Kompleksitas Ilmu Tafsir Dalam Literatur ‘Ulūm Alqur’ān - Muhammad Anshori (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
This paper attempts to explain the conditions of a mufassir/interpreter that had been formulated byMuslim scholars. These conditions are usually related to the sciences that must be mastered by an interpreter to avoid mistakes when interpreting the Qur'an. The requirements of aninterpreter are generally found in the literatures of the Qur'anic sciences, or commonly referred to as the 'Ulūm Al-Qur'ān. Therefore, this paper also explains the history of the emergence and development of the sciences of the Qur'an. The sciences that must be mastered by an interpreter are quite numerous and varied, but some scholars summarized them into just a few points. In contrast to the context of the previous scholars, in the present context, an interpreter must also master the social sciences of humanities and modern sciences. Of course this will greatly help someone in understanding the verses of the Qur'an itself.